Micro laser metal wire deposition for additive manufacturing of thin-walled structures - Demir, Ali Gökhan (Optics and lasers in engineering, 2018)
•A DED system based on the use of a pulsed laser beam and thin wires was developed.•Layer widths and heights were between 700–800 µm and 300-375 µm respectively.•Thin-walled structures with aspect ratio up to 20 were manufactured successfully.•The material use efficiency was observed to be close to 100%.•Manufacturing of inclined walls, tubular and conical parts were demonstrated. In this work, the micro laser metal wire deposition (µLMWD) process is studied as an additive manufacturing process for manufacturing thin walled structures with high aspect ratio. The developed µLMWD system consisted of a flash-pumped Nd:YAG laser source operating with ms-long pulses and an in-house developed wire feeding system. Processing conditions were investigated for single and multi-layer deposition in terms of geometry, microhardness and material use efficiency. Thin-walled structures with aspect ratio up to 20 were manufactured successfully, where layer width was between 700 and 800 µm. In multi-layer deposition conditions, the material use efficiency was observed to be close to 100%. The microhardness over the build direction was homogenous. The results show that the µLMWD process yields geometrical resolution close to powder-bed additive manufacturing processes, while maintaining the benefits of using wire feedstock.